Proceedings of the Workshop on Physics at the Japan Hadron Facility (JHF) : Adelaide, Australia, 14-21 March 2002 - Guzey, V. (Vadim) (World Scientific, 2002)
This volume outlines the exciting new opportunities in hadron physics which have been created by the Japan Hadron Facility (JHF), a major joint initiative between High Energy Accelerator Research Organization (KEK) and Japan Atomic Energy Research Institute (JAERI). The topics covered include unprecedented possibilities of studying strange matter, neutrino oscillations and hadron structure. The close interaction with lattice QCD is emphasised.